Role of Microfinance in Development of MSMEs and Economic Empowerment in India - Paridhi Gupta (Innovative Research Thoughts, 2025)
The microfinance sector has been providing huge impetus to the unorganized sector, driving small businesses, creating jobs and transforming the lives of millions of beneficiaries. The Microfinance sector has its own set of challenges ranging from lack of formal credit history, absence of collateral, laborious customer acquisition process and low digital and financial literacy.3 This paper explores the role and impact of microfinance in India and the discussion delves into the evolution of microfinance in India, its challenges, regulatory frameworks, and the overall impact on growth of small and medium scale industries and socio economic development.